SIMULATION OF A PHOTOVOLTAIC PANELS BY USING MATLAB/SIMULINK - Kocalmis Bilhan, Ayse; Caliskan, Abuzer; Unal, Sencer (Ieee, 2016)
In recent years, it is getting attention for renewable energy sources such as solar energy, fuel cells, batteries or ultracapacitors for distributed power generation systems. This paper proposes a general mathematical model of solar cells and Matlab/Simulink software based simulation of this model has been visually programmed. Proposed model can be used with other hybrid systems to develop solar cell simulations. Also, all equations are performed by using Matlab/Simulink programming.
8th International Conference on Electronics, Computers and Artificial Intelligence (ECAI) -- JUN 30-JUL 02, 2016 -- Ploiesti, ROMANIA
Keywords: Generalized model; PV cell; PV modeling